Hubungan Gender Role Attitude dengan Father Involvement pada Ayah yang Bekerja sebagai Petugas Pemadam Kebakaran di Kota Payakumbuh - Nursamsiah; Zulian Fikry (Jurnal Ragam Pengabdian, 2026)
This study aims to determine the relationship between gender role attitudes and father involvement among fathers who work as firefighters in Payakumbuh City. This study uses a quantitative method with a correlational design. The sampling technique used is total sampling, with all field firefighters in Payakumbuh City who have children as subjects, totaling 30 people. The scales used were the Attitude Toward Women Scale (ATWS) developed by Spence and Helmreich (1978) to measure gender role attitudes with a reliability of 0.696, and the Inventory of Father Involvement (IFI) developed by Hawkins et al. (2002) and adapted by Fajriati and Kumalasari (2021) to measure father involvement with a reliability of 0.985. The data were analyzed using simple linear regression with the help of SPSS. The results showed no significant relationship between gender role attitude and father involvement (p = 0.440; R² = 0.021). The majority of subjects were in the high father involvement category (83.3%) with a moderate gender role attitude that tended to be traditional. These findings indicate that in the context of the firefighting profession, contextual factors such as work stress are more dominant than gender role attitudes in influencing father involvement